Altered regional homogeneity and functional connectivity of brain activity in young HIV-infected patients with asymptomatic neurocognitive impairment - Han, Shuai; Aili, Xire; Ma, Juming; Liu, Jiaojiao; Wang, Wei; Yang, Xue; Wang, Xi; Sun, Lijun; Li, Hongjun (Frontiers in Neurology, 2022)
Objective Asymptomatic neurocognitive impairment (ANI) is the predominant form of cognitive impairment in young HIV-infected patients. However, the neurophysiological mechanisms in this disorder has not been clarified. We aimed to evaluate the altered patterns of functional brain activity in yong HIV-infected patients with ANI by quantifying the regional homogeneity (ReHo) and region of interest (ROI)-based functional connectivity (FC). Methods The experiment involved 44 young HIV-infected patients with ANI and 47 well-matched healthy controls (HC) undergoing resting-state functional magnetic resonance imaging (rs-fMRI) and neurocognitive tests. Reho alterations were first explored between ANI group and HC group. Subsequently, several regions showing differences in ReHo were defined as ROIs for FC analysis. Finally, correlation of ReHo and FC with cognitive function and clinical variables was assessed. Results Compared with HC, the ANI patients had significantly ReHo decrease in the right lingual gyrus (LING.R), right superior occipital gyrus (SOG.R), left superior occipital gyrus (SOG.L), left middle occipital gyrus (MOG.L), right middle frontal gyrus (MFG.R) and cerebellar vermis, as well as ReHo enhancement in the left middle frontal gyrus (MFG.L) and left insula (INS.L). The ANI patients showed increased FC between the LING.R and MOG.L compared to HC. For ANI patients, the verbal and language scores were negatively correlated with increased mean ReHo values in the MFG.L. Increased mean ReHo values in the INS.L were positively correlated with the disease duration. The mean ReHo values in the LING.R were positively correlated with the abstraction and executive function scores. Increased FC between the LING.R and MOG.L were positively correlated with verbal and language performance. Conclusion: The results suggest that the visual network might be the most vulnerable area of brain functions in young HIV-infected patients with ANI. The middle frontal gyrus, cerebellar vermis and insula also played an important role in asymptomatic neurocognitive impairment. The regional homogeneity and functional connectivity of these regions have compound alterations, which may be related to the course of disease and neurocognitive function. These neuroimaging findings will help us to understand the characteristics of brain network modifications in young HIV-infected patients with ANI.